Thromboembolic outcomes after use of a four‐factor prothrombin complex concentrate for vitamin K antagonist reversal in a real‐world setting. Issue 4 (20th November 2015) - Joseph, Ranjit; Burner, James; Yates, Sean; Strickland, Amanda; Tharpe, William; Sarode, Ravi
Abstract : BACKGROUND: A four‐factor prothrombin complex concentrate (4F‐PCC) was recently licensed in the United States for urgent vitamin K antagonist (VKA) reversal based on two randomized clinical trials. These studies excluded patients at high risk of thrombosis; therefore, the risk of thrombotic complications in unselected patients remains a concern. STUDY DESIGN AND METHODS: This study retrospectively evaluated the incidence of thromboembolic events (TEEs) and death in patients who received 4F‐PCC for VKA reversal. The study included 113 consecutive patients who were 18 years of age and older and were administered 4F‐PCC for VKA reversal. The incidence of TEE and deaths was evaluated for up to 60 days after PCC administration or until the end of hospitalization, whichever came later. RESULTS: Seven (6.2%) patients developed TEEs and 17 (15%) patients died. PCC administration was probably related to TEE and subsequent death in two (1.8%) patients. Multivariate analysis revealed that a diagnosis of Factor V Leiden or antiphospholipid syndrome was predictive of TEE, and active malignancy was predictive of death. CONCLUSION: This study supports the safety of 4F‐PCC for urgent VKA reversal even in unselected patients. The underlying type of hypercoagulable state and the dose of PCC may influence the incidence of TEE.